دور تطبيقات الذكاء الاصطناعي في تنمية المهارات التدريسية لدى معلمي ما قبل الخدمة بكلية التربية في جامعة صحار. - حمد حمود علي العي محمد آزرین بن محم فريد أوي (Arts Magazine, 2026)
This study examined how artificial intelligence applications contribute to the development of teaching skills among pre-service teachers at the Faculty of Education, Sohar University. Using a descriptive-analytical approach, data were collected from 44 participants through an electronic questionnaire structured around three dimensions: lesson planning, implementation, and evaluation. The findings showed that AI tools had a strong impact across all areas, with average scores of 4.08 for planning, 4.14 for implementation, and 3.95 for evaluation, each reflecting a high level of effectiveness. These results confirm that AI applications play a significant role in enhancing core teaching competencies, though they also highlight the need for continued integration and refinement to maximize their educational value.